Design and analysis of three wheel prototype car chassis - Amirul, Ramlan (2012)
This thesis presented about design and analysis of three wheel prototype car chassis for Shell Eco Marathon Asia 2012 competition. Base on the Existing Model, there have a few improvement to be done. First thing is to reduce the weight of the chassis where appropriate by designing more compact car. Secondly, this study also conduct to overcome the worst bending displacement where occur at driver cockpit, and lastly to provide extra large engine spaces where the Existing Design only have very limited spaces. Corresponds to the project background and problem statements, it is decided that the objectives of the project are to analyze and improve the existing car chassis based on Shell Eco Marathon Asia 2012 requirement, to redesign and proposed new chassis of prototype car which able to withstand the load applied on the chassis structure with minimum bending displacement, and to simulate the design using FEA software. The Project scopes are to study the concept of prototype car category for Shell Eco Marathon Asia 2012 Event, and evaluating with analysis the existing car design for previous competition. This project also covers to redesign three optional chassis of prototype car for Shell Eco Marathon Asia 2012, to analyze the optional chassis using FEA software, requirement to study was focus on static condition and stress simulation analysis only, and to select the best option which is capable to be fabricated at UMP. Three different chassis models have been designed by using Solidwork 2012. Then, analyzed by using Finite Element Analysis: Algor 23.1 software. Three parameters have been set up which are the weights of the chassis, the bending displacement of the chassis members, and the worst stress occurs on the chassis structure. The comparison result proves that the new proposed design in Model 2 is lighter than the Existing Model and the decrement is about 13.89% and the bending of the structure of new Design 2 was decreased too. Thus, the objectives of the project were achieved and the design has been proposed to Shell Eco Marathon Asia 2012 Team.